The Social Gospel in American Religion : A History - Evans, Christopher Hodge, 1959- (Book collections on Project MUSE., 2017)
This book is a remarkable history of the powerful and influential social gospel movement. The global crises of child labor, alcoholism and poverty were all brought to our attention through the social gospel movement. Its impact on American society makes it one of the most influential developments in American religious history. Christopher H. Evans traces the development of the social gospel in American Protestantism, and illustrates how the religious idealism of the movement also rose up within Judaism and Catholicism. Contrary to the works of previous historians, Evans demonstrates how the presence of the social gospel continued in American culture long after its alleged demise following World War I. Evans reveals the many aspects of the social gospel and their influence on a range of social movements during the twentieth century, culminating with the civil rights movement in the 1950s and 1960s. It also explores the relationship between the liberal social gospel of the early twentieth century and later iterations of social reform in late twentieth century evangelicalism. The Social Gospel in American Religion considers an impressive array of historical figures including Washington Gladden, Emil Hirsch, Frances Willard, Reverdy Ransom, Walter Rauschenbusch, Stephen Wise, John Ryan, Harry Emerson Fosdick, A.J. Muste, Georgia Harkness, and Benjamin Mays. It demonstrates how these figures contributed to the shape of the social gospel in America, while arguing that the movement's legacy lies in its profound influence on broader traditions of liberal-progressive political reform in American history. - Publisher.